MODEL KESUKSESAN PRODUK SANITER - Andrean Emaputra dan Subagyo (Jurnal Teknosains, 2014)
A company that manufactures home decorations and sanitary products has not been able to achieve the expectedproduction utility. This was indicated by the installed production capacity (of the sink) in 2013, which has not beencompletely consumed. Therefore, studies that explore customer needs and their corresponding levels of customersatisfaction need to be done. Achieving the desired product quality and customer satisfaction can be an entrancefor achieving higher sales. This study was conducted in several stages, with the sink selected as the type of productfor the research object. First, the quality attributes of the sink were identified. Second, the importance levels ofthe quality attributes were searched by questionnaires. Third, the sink quality attributes were grouped into theclassification of quality attributes by the Kano model. This study gave some results. First, 90% of the averageimportance level of the sink quality attributes were between ‘important’ and ‘extremely important’. Second, thesurvey that used the Kano model indicated that (1) ‘performance’ was a must-be quality attribute, (2) ‘aesthetics’was not an indifferent quality attribute from ‘attractiveness’, except for ‘excellence drainage’, which was classifiedinto a must-be quality attribute, (3) features could improve customer satisfaction quickly through ‘the sink priceis competitive’, (4) the ‘durable sink color’ and ‘scratch resistant’ attributes can increase customer satisfaction, (5)‘materials that are for maintenance are included when buying the sink’ could increase consumer satisfaction veryquickly, and (6) the higher the reputation of the company, the higher the customer satisfaction